2010
DOI: 10.1111/j.1468-3083.2010.03624.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous angiosarcoma: own experience over 13 years. Clinical features, disease course and immunohistochemical profile

Abstract: Cutaneous AS was clinically diagnosed in 4 of 9 patients, while systemic lupus erythematosus was the most common misdiagnosis. Radiotherapy was the most prescribed treatment, but many different combinations of surgery, chemotherapy and radiotherapy were observed. Mean disease-free and overall survival (15.4 and 23.7 respectively) were consistent with previous series, with local recurrence rate (2/9) lower than previously reported data. CD31 was positive in all patients. Vimentin, D2-40 and VEGFR-3 were express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 15 publications
2
28
0
4
Order By: Relevance
“…6 Most tumors arise in middle-aged adults with a 0.5% rate of metastases. 6,[19][20][21] We found eight patients in our files, which have been described in detail recently. 6 In more than 90% of cases, a unique translocation Figure 2 Advanced angiosarcoma with regional lymph node involvement involving chromosomes 17 and 22 has been detected, leading to a fusion product COL1A1-PDFGB, which results in upregulation of platelet-derived growth factor beta -a ligand for transmembrane receptor kinase.…”
Section: Discussionmentioning
confidence: 84%
“…6 Most tumors arise in middle-aged adults with a 0.5% rate of metastases. 6,[19][20][21] We found eight patients in our files, which have been described in detail recently. 6 In more than 90% of cases, a unique translocation Figure 2 Advanced angiosarcoma with regional lymph node involvement involving chromosomes 17 and 22 has been detected, leading to a fusion product COL1A1-PDFGB, which results in upregulation of platelet-derived growth factor beta -a ligand for transmembrane receptor kinase.…”
Section: Discussionmentioning
confidence: 84%
“…[5][6][7] Patients' prognosis, however, remains poor with a 5-y survival of approximately 10% to 20% due to the eventual formation of distant metastases. [8][9][10] The development of more effective treatments is therefore required, and immunotherapy could be a therapeutic option. Fujii et al reported that antitumor immunity with CD8 C T cells in tumor-infiltrating lymphocytes (TILs) is important to prevent the progression of CAS.…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous angiosarcoma (AS) is a rare malignant tumor of soft tissue and is known to have three clinical subtypes: classical AS (head and neck type), Stewart–Treves syndrome, and post‐radiation AS . Few dermoscopic features of AS have been reported and it has not yet been examined in detail.…”
mentioning
confidence: 99%